Plan De Desarrollo Turístico Como Alternativa De Dinamismo Socio Economico En La Parroquia Nueva Loja, Cantón Lago Agrio, Provincia De Sucumbíos - Grefa, Edith Jessica Cerda; Bernal, Catalina Margarita Verdugo; Guerra, Juan Hugo Rodríguez; Sampedro, Otto Fernando Balseca; Moyota, Paulina Beatriz Díaz; Paredes, Oscar Iván Granizo; Layedra, Jaime Robert Guevara (European Scientific Journal, ESJ, 2017)
This paper elaborates a plan for tourist development in the county of Nueva Loja, canton Lago Agrio, province of Sucumbíos, Ecuador, which was based on bibliographic review, field trips and participatory workshops. These steps validated a diagnosis related to physical, cultural, socioeconomic, and political dimensions of the territory. The inventory of tourist attractions in Nueva Loja followed the methodology of the Ecuador Ministry of Tourism, 2004, resulting in identification of seven natural attractions, up to Level II, and seven intangible cultural attractions. To determine the profile of domestic and foreign tourists wishing to get to know the county, a concurrent market survey was conducted. A situational analysis was carried out, in which institutions associated with economic development in the county were identified, as well as policies, objectives and strategies that serve to strengthen tourism in the region. To ensure the sustainability of four programs and ten projects, an investment of USD 454,700 is required. The plan establishes a basis for improving tourism, under a scheme of sustainability, resulting in economic benefits that will be experienced by its inhabitants. The implementation of the plan is recommended, since it is designed according to the needs and the local reality for the sustainable development of tourism.